Modeling and Simulation of Satellite Communication System Base on MBSE - Wenping LI; Hefeng BAI; Yi ZHAO; Leilei WU; Xiaoting WANG (天地一体化信息网络, 2021)
A method based on model-based systems engineering (MBSE) for the demonstration, top-level design and engineering construction of the satellite communication system was introduced, which was aim at the problem of design, description, verification and validation in the construction and application of complex satellite communication system.According to the system design standard base on department of defense architecture framework (DoDAF), the system views (SV) such as function model, node model and process model were built by using the system architecture (SA) design software.Through the digital simulation based on model driven and the analysis of simulation data, the correctness, rationality and feasibility of the system design were verifi ed.The results showed that this method can eff ectively identify risks in the system design stage, verify and confi rm the design scheme, and provide strong support for project demonstration, top-level design and engineering construction of satellite communication system.